The immortal Irishman [compact disc, unabridged] : the Irish revolutionary who became an American hero - Egan, Timothy (Brilliance Audio, 2016)
Places the improbable life of Great Famine orator and revolutionary hero Thomas Francis Meagher against a backdrop of Irish-American history, detailing his leadership during Irish uprisings, service with the Irish Brigade and achievements as the territorial governor of Montana